2012
DOI: 10.1371/journal.pone.0037603
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of HIV: Empirical Support for Jail-Based Screening

Abstract: BackgroundAlthough routine HIV testing is recommended for jails, little empirical data exist describing newly diagnosed individuals in this setting.MethodsClient-level data (CLD) are available on a subset of individuals served in EnhanceLink, for the nine of the 10 sites who enrolled newly diagnosed persons in the client level evaluation. In addition to information about time of diagnosis, we analyzed data on initial CD4 count, use of antiretroviral therapy (ART), and linkage to care post discharge. Baseline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…This cohort has been described across many domains, including HIV treatment outcomes, 39 new HIV infections, 3 longitudinal retention in care, 14 gender differences in service needs 40 and HIV treatment outcomes, 41 pre-and post-release homelessness, 20,35 recidivism, 22 and SUDs. 17,36 Health care utilization among this cohort has not previously been described.…”
Section: Setting and Selection Of Participantsmentioning
confidence: 99%
“…This cohort has been described across many domains, including HIV treatment outcomes, 39 new HIV infections, 3 longitudinal retention in care, 14 gender differences in service needs 40 and HIV treatment outcomes, 41 pre-and post-release homelessness, 20,35 recidivism, 22 and SUDs. 17,36 Health care utilization among this cohort has not previously been described.…”
Section: Setting and Selection Of Participantsmentioning
confidence: 99%
“…4–6 New positives in correctional facilities also have reported riskier behavior, including sex with someone other than their main partner, unsafe vaginal/anal sex, and sex with an at-risk partner (i.e., injected drugs, HIV-infected, or men who have sex with men). 5,7 …”
mentioning
confidence: 99%
“…Rapid opt-out HIV testing at jails helps identify new HIV cases that may have otherwise progressed to a later stage of the disease. A previous study in which FCJ participated showed that HIV screening at jails detected cases in earlier courses of disease compared with screening at other types of venues; 28 the present study did not assess disease stage at diagnosis. Jail screening programs clearly benefit the newly diagnosed.…”
Section: Discussionmentioning
confidence: 64%